2012
DOI: 10.1039/c2ja10319b
|View full text |Cite
|
Sign up to set email alerts
|

Towards chloramphenicol detection by inductively coupled plasma mass spectrometry (ICP-MS) linked immunoassay using gold nanoparticles (AuNPs) as element tags

Abstract: This paper describes the feasibility for trace analysis of chloramphenicol using a novel immunoassay by coupling competitive measurement of chloramphenicol (CAP) to ICP-MS by the use of CAP labeled with AuNPs. Polyclonal rabbit anti-mouse immunoglobulins (anti-mouse IgG) were pre-coated on the 96-well polystyrene microplate solid support to allow the retention of mouse monoclonal to chloramphenicol (MAb-anti-CAP) antibody-CAP on the plates. Samples containing CAP as an antigen premixed with CAP-BSA protein lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…2.2 μg g -1 (peanut matrix) (Careri, et al, 2007;Careri, et al, 2008) CEA Magnetic beads/Sandwich Hg labeled antibody 0.041 ng mL -1 Goat anti E. coli Microwells Iodine labeled antibody 120 ng mL -1 (Li et al, 2010) Rabbit anti-human IgG Microwells/Sandwich Au NPs labeled antibody 0.4 ng mL -1 (Zhang, et al, 2002) Human IgG (Baranov, et al, 2002) Human vascular endothelial growth factor Microwells/Sandwich Au NPs labeled antibody 0.029 ng mL -1 (Thompson, et al, 2010) Anti-erythropoietin antibody Microwells/Sandwich Au NPs labeled antibody 10.7 ng mL -1 (Lu, et al, 2009) Ochratoxin A Microwells/Competitive Au NPs labeled antibody 0.003 ng mL -1 (Giesen et al, 2010) Peptide-modified DNA Nitrocellulose membrane/Noncompetitive Au NPs labeled antibody 0.2 pmol (Merkoci, et al, 2005) Virus-specific RNA Magnetic beads/Sandwich Au NPs labeled oligonucleotide probe 80 zmol (Hsu, et al, 2011) Human α-thrombin Magnetic beads/Sandwich AuNPs labeled aptamer 0.5 fmol (Zhao, et al, 2009) E. coli O157:H7 cell Homogeneous Au NPs labeled antibody 500 CFU mL -1 (Li, et al, 2010) Chloramphenicol Microwells/Competitive Au NPs labeled antibody 4.52 ng mL -1 (Jarujamrus, et al, 2012) Human IgG Immunoaffinity chromatography/Sandwich CdSe NPs labeled antibody 0.058 ng mL -1 (Cd), 0.097 ng mL -1 (Se) (Chen, et al, 2010) AFP Microwells/Competitive with single particle ICPMS Au NPs labeled antibody 0.016 ng mL -1 (Hu, et al, 2009) Rabbit-anti-human IgG Microwells/Sandwich with single particle ICPMS Au NPs labeled antibody 0.1 ng mL -1 (Liu, et al, 2010) DNA Homogenous/Sandwich with single particle ICPMS Au NPs labeled antibody 1 pmol (Han, et al, 2011) Smad2, Smad4, Human IgG, Met-3xFLAG™-BAP Microwells/Maleylation AuNPs and Eu labeled antibody - (Quinn, et al, 2002) AFP hCG Microwells/Sandwich Eu labeled antibody Sm labeled antibody 1.2 ng mL -1 1.7 ng mL -1 (Zhang, et al, 2004) Growth factor PDGF-AA 3.0 mIU mL -1 2.6 ng mL -1 (Terenghi, et al, 2009) nanoparticle detection is that high sensitivity can be easily obtained because of large quantities of detectable atoms in each nanoparticle tag (for instance, ca. 30,000 Au atoms in an Au NPs of 10 nm diameter).…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 μg g -1 (peanut matrix) (Careri, et al, 2007;Careri, et al, 2008) CEA Magnetic beads/Sandwich Hg labeled antibody 0.041 ng mL -1 Goat anti E. coli Microwells Iodine labeled antibody 120 ng mL -1 (Li et al, 2010) Rabbit anti-human IgG Microwells/Sandwich Au NPs labeled antibody 0.4 ng mL -1 (Zhang, et al, 2002) Human IgG (Baranov, et al, 2002) Human vascular endothelial growth factor Microwells/Sandwich Au NPs labeled antibody 0.029 ng mL -1 (Thompson, et al, 2010) Anti-erythropoietin antibody Microwells/Sandwich Au NPs labeled antibody 10.7 ng mL -1 (Lu, et al, 2009) Ochratoxin A Microwells/Competitive Au NPs labeled antibody 0.003 ng mL -1 (Giesen et al, 2010) Peptide-modified DNA Nitrocellulose membrane/Noncompetitive Au NPs labeled antibody 0.2 pmol (Merkoci, et al, 2005) Virus-specific RNA Magnetic beads/Sandwich Au NPs labeled oligonucleotide probe 80 zmol (Hsu, et al, 2011) Human α-thrombin Magnetic beads/Sandwich AuNPs labeled aptamer 0.5 fmol (Zhao, et al, 2009) E. coli O157:H7 cell Homogeneous Au NPs labeled antibody 500 CFU mL -1 (Li, et al, 2010) Chloramphenicol Microwells/Competitive Au NPs labeled antibody 4.52 ng mL -1 (Jarujamrus, et al, 2012) Human IgG Immunoaffinity chromatography/Sandwich CdSe NPs labeled antibody 0.058 ng mL -1 (Cd), 0.097 ng mL -1 (Se) (Chen, et al, 2010) AFP Microwells/Competitive with single particle ICPMS Au NPs labeled antibody 0.016 ng mL -1 (Hu, et al, 2009) Rabbit-anti-human IgG Microwells/Sandwich with single particle ICPMS Au NPs labeled antibody 0.1 ng mL -1 (Liu, et al, 2010) DNA Homogenous/Sandwich with single particle ICPMS Au NPs labeled antibody 1 pmol (Han, et al, 2011) Smad2, Smad4, Human IgG, Met-3xFLAG™-BAP Microwells/Maleylation AuNPs and Eu labeled antibody - (Quinn, et al, 2002) AFP hCG Microwells/Sandwich Eu labeled antibody Sm labeled antibody 1.2 ng mL -1 1.7 ng mL -1 (Zhang, et al, 2004) Growth factor PDGF-AA 3.0 mIU mL -1 2.6 ng mL -1 (Terenghi, et al, 2009) nanoparticle detection is that high sensitivity can be easily obtained because of large quantities of detectable atoms in each nanoparticle tag (for instance, ca. 30,000 Au atoms in an Au NPs of 10 nm diameter).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Almost at the same time, Baranov et al investigated four different ICPMS-based immunoassays (using centrifugal filtration, protein A affinity, size exclusion gel filtration, and ELISA) by employing Au nanoparticles and Eu ions tags to produce a fast and efficient means for detecting proteins of interest with exceptional sensitivity and precision in complicated biological samples (Baranov et al, 2002a). Thanks to the high sensitivity endowed by Au nanoparticles, ICPMS-based bioassay have found applications for different analytes, including chloramphenicol (Jarujamrus et al, 2012), c-myc peptide contained oligonucleotides (Merkoci et al, 2005), virus-specific RNA (Hsu et al, 2011), anti-erythropoietin antibodies (Lu et al, 2009), human alpha-thrombin (Zhao et al, 2009b), human vascular endothelial growth factor (Thompson et al, 2010), and even Escherichia coli O157:H7 bacteria (Li et al, 2010a).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Zhang et al [12] and Tanner et al [13] reported the pioneer work about various kinds of ICPMS-based metalloimmunoassays by Au nanoparticles [14][15][16][17][18][19][20][21][22] labeling. CdSe quantum dots [23], PbS quantum dots [24] and silver nanoparticles [25] were employed by Hu et al for disease biomarker quantification by ICPMS.…”
Section: Introductionmentioning
confidence: 98%
“…In veterinary practice, chloramphenicol has been used extensively as an antibiotic against bacterial infections in chickens, calves, cows and pigs . However, chloramphenicol use is prohibited when breeding animals, because chloramphenicol (ingested via foodstuffs) is highly toxic to humans, with adverse effects such as bone marrow depression and aplastic anemia . In many countries, including China, a zero tolerance policy has been established for the presence of CAP residues in meat and animal products .…”
Section: Introductionmentioning
confidence: 99%